Effect of Growth Hormone Therapy on a 4-Year-Old Girl with Pfeiffer Syndrome and Short Stature: A Case Report - Min Jeong Jang; Moon Bae Ahn (MDPI AG, 2022)
Fibroblast growth factor receptors (FGFRs) are expressed in epiphyseal cartilage cells of developing bones and regulate endochondral bone formation with interdependent signaling pathways. Gene mutation in FGFRs disrupts the formation of endochondral bony structure by reducing the number of proliferating chondrocytes. Among the syndromes caused by mutation in the FGFR gene, Pfeiffer syndrome is a rare inherited disease characterized by acrocephalosyndactyly related to hypertelorism, broad pollex, and hallux. We describe the case of a 4-year-old girl with short stature, advanced bone age, wide thumbs and great toes. The patient was diagnosed with partial growth hormone deficiency and an identified mutation in the FGFR2 gene. Standard deviation score of her height increased after starting growth hormone therapy. This report will raise awareness of the growth hormone provocation test regardless of bone age in patients with short stature founded FGFR gene mutation.